A importância da biografia na construção da interpretação das obras de Lycia de Biase (1910-1991) - Lorenção, Tayná Batista; Freitas, Alexandre Siqueira de (Farol, 2023)
Lycia De Biase was a musician from Espírito Santo who worked actively in the musical circle in the 1930s, she produced 426 compositions throughout her life. There are still few researches dedicated to studying her production, so this article aims to investigate possible aspects of the technique and aesthetics of the composer as an aid for future studies of interpretation of her works. This will be done through observations of biographical data obtained by LORENÇÃO (2020) and GARCIA (2021).
Keywords: Lycia De Biase; Biography; Musicology; Creation process.